306 Outcomes after the regionalization of care for high risk endometrial cancers: a population-based study. (13th November 2020) - Nica, A; Sutradhar, R; Kupets, R; Covens, A; Vicus, D; Li, Q; Ferguson, S
Abstract : Objectives: In June 2013, the agency responsible for advancing cancer care in Ontario, Canada, published practice guidelines recommending that gynaecologic oncologists (GOs) at designated centers manage the treatment of patients with high grade endometrial cancers. This study examines the effects of this regionalization of care on patient outcomes. Methods: In this retrospective cohort study, patients diagnosed with non-endometrioid high risk endometrial cancer (serous, carcinosarcoma, clear cell, undifferentiated) from 2003–2017 were identified using province-wide administrative databases. Results: We identified 3518 patients with high risk endometrial cancer. The case mix as represented by patient comorbidities and disease stage distribution did not differ significantly between the two regionalization periods. There was a significant increase (69% to 85%, p<0.001) in the proportion of primary surgeries performed by GOs after regionalization, which was not explained by secular trends. After regionalization, the proportion of patients who had surgical staging (50% to 63%, p<0.001), and the proportion of patients who received adjuvant treatment (65% to 71%, p<0.001) increased significantly. After adjusting for age, stage, and comorbidities, there was an increase in overall survival (HR 0.85 (0.73–0.99), p=0.04) after regionalization. Conclusions: The publication of a regionalization policy for the treatment of high risk histology endometrial cancers in Ontario led to an increase in the proportion of surgeries performed by GOs, surgical staging and adjuvant treatment. This also translated into a significant improvement in patient survival.